Enhancing therapeutic antibody production through amino acid-induced pH shift in Protein A affinity chromatography - Lin, Senzhu; Wang, Yue (Frontiers in Bioengineering and Biotechnology, 2025)
Protein aggregation, denaturation, and loss of potency often occur during Protein A chromatography due to the harsh acidic conditions required for antibody elution. This study presents a pH shift-based elution strategy that effectively mitigates these issues by introducing amino acid-based elution buffers to create a milder elution environment and increase the final elution pH. By optimizing the combination of pre-elution and elution buffers, the elution pool pH was increased up to 7.2, significantly enhancing protein stability. Among various elution buffers tested, amino acids with non-polar or polar uncharged side chains—such as leucine, glycine, and serine—exhibited the most effective pH transition, resulting in 0.5–2.9 units pH shifts. Additionally, the use of 50 mM Bis-Tris, pH 7.2 as a pre-elution buffer demonstrated the highest capacity for stabilizing pH shifts. The scalability of this approach was validated using a 10 cm diameter column, where yields remained comparable to small-scale experiments, and elution pool stability was able to be maintained for 72 h at 26°C. These findings establish pH-shifting elution as a scalable, cost-effective method for improving the recovery and stability of low pH-unstable therapeutic antibodies in Protein A chromatography.